Postoperative Cardiac Arrest after Heart Surgery: Does Extracorporeal Perfusion Support a Paradigm Change in Management? - Edward Gologorsky; Francisco Igor B. Macedo; Enisa M. Carvalho; Angela Gologorsky; Marco Ricci; Tomas A. Salerno (Anesthesiology Research and Practice)
Early institution of extracorporeal perfusion support (ECPS) may improve survival after cardiac arrest. Two patients sustained unexpected cardiac arrest in the Intensive Care Unit (ICU) following cardiac interventions. ECPS was initiated due to failure to restore hemodynamics after prolonged (over 60 minutes) advanced cardiac life support (ACLS) protocol-guided cardiopulmonary resuscitation. Despite relatively late institution of ECPS, both patients survived with preserved neurological function. This communication focuses on the utility of ECPS in the ICU as a part of resuscitative efforts.